2020
DOI: 10.1002/ejhf.1866
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG PET/CT brain glucose metabolism as a marker of different types of depression comorbidity in chronic heart failure patients with impaired systolic function

Abstract: Aims Depression is an important issue in heart failure (HF). The study investigated whole‐brain and regional brain glucose metabolism in HF patients and its association with depression comorbidity. Methods and results Twenty‐nine hospitalized patients with symptomatic systolic HF (left ventricular ejection fraction <40%), New York Heart Association (NYHA) class II–IV and mean age of 55.5 ± 12.0 years, had psychometric questionnaires before discharge and an 18F‐FDG PET/CT brain scan after discharge. Semi‐automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…1 Recently, Lyra et al investigated brain glucose metabolism in patients with HF using FDG PET/CT. 18 In their study, patients with HF showed whole-brain and regional brain hypometabolism compared to that in matched controls, similar to the findings of the study by Yun and colleagues. Furthermore, patients with HF and epiphenomenal or real depression showed different metabolic patterns with significant relative regional brain hypometabolism in the amygdala, hippocampus, and ventral prefrontal cortex implicated in the pathogenesis of depression.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…1 Recently, Lyra et al investigated brain glucose metabolism in patients with HF using FDG PET/CT. 18 In their study, patients with HF showed whole-brain and regional brain hypometabolism compared to that in matched controls, similar to the findings of the study by Yun and colleagues. Furthermore, patients with HF and epiphenomenal or real depression showed different metabolic patterns with significant relative regional brain hypometabolism in the amygdala, hippocampus, and ventral prefrontal cortex implicated in the pathogenesis of depression.…”
supporting
confidence: 84%
“…Although biochemical markers have received considerable attention for Alzheimer's disease in recent years, Kresge et al found an interaction between the left ventricular ejection fraction (LVEF) and cerebrospinal fluid biomarkers in participants with normal cognition, whereas lower LVEF is associated with increased total tau and phosphorylated tau. 11 In this issue of the Journal of Nuclear Cardiology, Yun and colleagues report their investigation of the metabolic heart-brain interaction in patients with HF with a reduced ejection fraction using 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT). The importance of this study is in determining if there is a relationship between cardiac function and the cerebral metabolic activity derived from FDG PET/CT in comparison with that in healthy volunteers.…”
mentioning
confidence: 99%
“…Theoretically, patients with stable and chronic HF may be more similar to the general population ( 31 ). Conversely, in patients recently hospitalized with acute HF, secondary depression due to severe somatic disorders ( 32 ) may surpass the effects of a higher BMI and younger age. In this study, COPD and diabetes mellitus were independent predictors of post-discharge depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the deficiency of energy substrates forces the brain to make adaptive changes in the utilization of glucose. A great number of studies have reported that depression impaired brain energy metabolism, ,, but the detailed mechanism is not clear. Therefore, the supply of energy substrates is indispensable for revealing brain energy metabolism disorders in depression.…”
Section: Discussionmentioning
confidence: 99%